A docência do ensino fundamental I no período pandêmico e pós-pandêmico: uma análise de produções acadêmicas entre os anos de 2020 e 2024 - Covre, Luciana Mara (Universidade Federal de São Carlos, 2025)
This study advocates for the valorization of teaching as a profession, the recognition of the knowledge mobilized in teaching practice, and the strengthening of the professionalization movement in our country. Its relevance lies in its effort to highlight the driving force that motivated teachers during the COVID-19 pandemic period in which a new institutional order was established in schools, leading to radical changes in educational proposals and interpersonal relationships. In this context, the following research question was formulated: What do academic publications reveal about the challenges faced in professional practice by elementary school teachers (grades 1 to 5) during the pandemic? To address this question, the study aimed to present a bibliographic review of academic works produced between 2020 and 2024 on the challenges encountered in the professional practice of elementary school teachers during and after the pandemic. To develop the study, authors aligned with the epistemology of professional practice were utilized, following a qualitative and exploratory-descriptive approach, guided by a literature review of the field. The goal was to highlight how literature addressed the challenges faced in professional practice by elementary school teachers during this period. The analysis results point to striking similarities in the challenges faced by teachers in both the pandemic and post-pandemic contexts. These include: the constant need for teachers to adapt; difficulties in using and accessing technological and digital tools; the lack of training policies that are better integrated with the school reality; emotional overload caused by fear and anxiety experienced during the crisis; physical exhaustion due to excessive workload and the merging of home and work environments; and the emergence of collaborative practices as strategies to cope with the challenges imposed by the new social order. These aspects lead us to understand that teaching is not merely about acquiring techniques, but involves the mobilization and production of plural, composite, and heterogeneous knowledge constructed through practice, mediated by time, and shaped by historical and social contexts. However, this work assumes the need to create institutional and political conditions that support teacher training and professional practice in a dignified and continuous manner, especially in the face of daily uncertainties, innovations, difficulties, and catastrophic events such as the COVID-19 pandemic. This study fulfills its political and pedagogical role by analyzing this unique historical moment, exposing weaknesses in basic education and the lack of policies aimed at the professionalization of teaching. Thus, by analyzing reports and research, it becomes clear that—despite changing context structural challenges persist, requiring closer attention to the construction of teaching knowledge based on real, situated practice. The pandemic, with all its difficulties, revealed how essential it is to value teachers as reflective individuals and protagonists of their own professional development, reaffirming the inseparability of practice and training in the teaching profession.
Teaching in elementary school (grades 1 to 5) during the pandemic and post-pandemic period: an analysis of academic publications between 2020 and 2024
La docencia en la educación primaria en el período pandémico y pospandémico: un análisis de producciones académicas entre los años 2020 y 2024
Keywords: Professores do ensino fundamental I; Prática docente; Pandemia covid 19; Saberes da prática; Profissionalização docente; Elementary school teachers (grades 1 to 5); Teaching practice; Covid-19 pandemic; Knowledge from practice; Teacher professionalization; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade